Diyabet ve cinsel yaşam - Özcan, Levent; Polat, Emre Can (My University, 2015)
Diabetes mellitus en sık rastlanan kronik rahatsızlıktır. Diyabet hem erkek hem de kadınlarda cinsel fonksiyon bozukluğu nedenidir. Diyabetik olmayan erkeklerle karşılaştırıldığında diyabetik erkeklerde 3 kat fazla erektil disfonksiyon görülmüştür. Kadınlarda diyabetin cinsel fonksiyonlar üzerine etkisi net olmamakla birlikte yapılan çalışmalarda diyabetik kadınlarda cinsel bozukluklar fazla görülmüştür. Bu makalenin amacı diyabetin cinsel fonksiyonlar üzerindeki etkisini tartışmaktır.

Diabetes mellitus is one of the most common chronic diseases. It has been associated with sexual dysfunction, both in males and in females. Diabetes is an established risk factor for sexual dysfunction in men, as a threefold increased risk of erectile dysfunction was documented in diabetic men, as compared with nondiabetic men. Among women, evidence regarding the association between diabetes and sexual dysfunction are less conclusive, although most studies have reported a higher prevalence of female sexual dysfunction in diabetic women as compared with nondiabetic women. This paper aims to discuss the impact of diabetes on sexual function.
Diabetes mellitus and sexual life
Keywords: Diabetes Mellitus; Erektil Disfonksiyon; Kadın Cinsel Disfonksiyonu; Erectile Dysfunction; Female Sexual Dysfunction